The Adoption of the E-Banking: Validation of the Technology Acceptance Model - Raida, Regaieg Essafi; Néji, Bouslama (Scientific Research, 2013)
This paper is based on the technology acceptance model which has been adopted by several previous researches. The purpose of the study is to determine the factors that explain the adoption of e-banking by professional in “Business to Business” relationships. It explores the determinants of use of the Internet in the relationship between bank and firm and it validates the model in Tunisian context. This paper has tested that perceived usefulness and perceived ease determine the attitude of the use, and that attitude determines the intent to use of e-banking by means of the multiple regressions. The originality of this study is the exploration of the determinants of use of e-banking by professional in order to promote its adoption.
Keywords: Bank on Internet; Perceived Usefulness; Perceived Ease; Intent to Use